2013
DOI: 10.1093/scan/nst043
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and emotion regulation—an fMRI study

Abstract: Mindfulness an attentive non-judgmental focus on present experiences is increasingly incorporated in psychotherapeutic treatments as a skill fostering emotion regulation. Neurobiological mechanisms of actively induced emotion regulation are associated with prefrontally mediated downregulation of, for instance, the amygdala. We were interested in neurobiological correlates of a short mindfulness instruction during emotional arousal. Using functional magnetic resonance imaging, we investigated effects of a short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(190 citation statements)
references
References 79 publications
9
174
0
7
Order By: Relevance
“…Furthermore, studies investigating trait mindfulness have reported that individuals with greater trait mindfulness exhibit lower AI activation during expectation of and exposure to negative stimuli. These results point toward reduced automatic emotional responding, 67,111 which could be expected to lead to reduced hyperarousal in individuals with PTSD if these results were replicated in this population.…”
Section: J Psychiatry Neurosci 2018;43(1)mentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, studies investigating trait mindfulness have reported that individuals with greater trait mindfulness exhibit lower AI activation during expectation of and exposure to negative stimuli. These results point toward reduced automatic emotional responding, 67,111 which could be expected to lead to reduced hyperarousal in individuals with PTSD if these results were replicated in this population.…”
Section: J Psychiatry Neurosci 2018;43(1)mentioning
confidence: 66%
“…Specifically, increased activation of the prefrontal cortex (including the dorsomedial PFC [dmPFC]) during expectation of negative pictures and reduced activation in the amygdala and parahippo campal gyrus following perception of negative stimuli has been observed following brief mindfulness training among healthy controls. 67 Similarly, a study investigating MBCT in the treatment of bipolar disorder reported increased activity in the mPFC during a mindfulness task following treatment as well as correlations between signal changes in the mPFC and mindfulness, as measured by the Five Factor Mindfulness Questionnaire (FFMQ). 68 Further studies have identified reduced amygdala reactivity in response to emotionally valenced images in healthy controls following a mindful attention group 69 and during an emotional processing task among novice meditators.…”
Section: Prefrontal Modulation Of Limbic Structures and Mindfulnessmentioning
confidence: 99%
“…Accumulating evidence suggests positive effects of mindfulness meditation on attentional processes and emotion regulation (see e.g. Chambers et al 2008;Chambers et al 2009;Jha et al 2007;Kabat-Zinn 2003;Lutz et al 2014;Valentine and Sweet 1999), cognitive flexibility (Moore and Malinowski 2009;Moore et al 2012), memory performance (Jha et al 2010;Mrazek et al 2013;Tang et al 2007;Zeidan et al 2010) and general well-being (e.g. Wallace and Shapiro 2006;Carmody and Baer 2008;Grossman et al 2008;Chiesa and Serretti 2009;Williams et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, os estudos apontam que a prática meditativa está associada a uma maior ativação do córtex cingulado anterior, cuja área é responsável pelo monitoramento de conflitos e pela regulação emocional através do controle cognitivo (Tang, Hölzel, & Posner, 2015). Também existem evidências de que a meditação ajuda a reduzir a reatividade da amígdala (AM) frente a estímulos emocionais negativos, cujo padrão é precedido por uma maior ativação do córtex pré-frontal dorsomedial e dorsolateral (Lutz et al, 2013). De modo similar, outro estudo mostrou que uma redução da percepção de estresse se correlacionou com uma menor densidade de massa cinzenta na AM direita (Hölzel et al, 2009).…”
Section: Discussionunclassified